Experimental Studies on Some Drugs Used in Covid-19 Treatment (Favipiravir and Dexamethasone) in Albino Rats - Abou El-Fetouh, Moustafa S.; El-Seddawy, Nora M.; Abdel Mageed, Manar A.; Abd El-Hamed, Mona N. (Journal of Advanced Veterinary Research, 2023)
In this study, the side effects of some anti-covid-19 drugs (Favipiravir and Dexamethasone) were evaluated through the pathological, and clinicopathological changes in the tissues of rats. 30 rats were divided into 6 groups (Gp1- control), (Gp2 received 0.54 mg/kg dexamethasone), (Gp3 received 200 mg/kg favipiravir), (Gp4 received 400 mg/kg favipiravir), (Gp5 received 200 mg/kg favipiravir + 0.54 mg/kg dexamethasone) and (Gp6 received 400 mg/kg favipiravir + 0.54 mg/kg dexamethasone). The histopathological and clinical results showed that both favipiravir and dexamethasone-induced lesions in the liver, kidney, and lung as well as increased liver functions (alanine transaminase, aspartate aminotransferase, and C-reactive protein) and kidney functions (Urea and creatinine). Also increased oxidative stress parameters such as malondialdehyde and decreased antioxidants in liver, and kidney tissues. The gene expression in splenic tissues showed an increase in NF-kb, IL6, and TNF when animals were exposed to 400 mg/kg favipiravir. While these genes (NF-kb, IL6, and TNF) decreased when animals received a combination of favipiravir with dexamethasone. In gp3, hydropic degeneration was noted in both the kidney and liver. In Gp4, necrotic changes in the liver, and vacuolation of the renal glomerular tufts were observed. In Gp5, the necrotic hepatic tissues were infiltrated with mononuclear cells, and necrosis and inflammation in renal tubules in the kidney were shown. In gp6, leukocytic infiltration was noted in both the kidney and liver. In conclusion, the anti-Covid-19 drugs could induce pathological changes in the internal organs of the rat.